Cognitive demands influence lower extremity mechanics during a drop vertical jump task in female athletes - Almonroeder, T. G.; Kernozek, T.; Cobb, S.; Slavens, B.; Wang, J.; Huddleston, W. (Journal of Orthopaedic & Sports Physical Therapy, 2018)
Study Design: Cross-sectional study. Background: The drop vertical jump task is commonly used to screen for anterior cruciate ligament injury risk; however, its predictive validity is limited. The limited predictive validity of the drop vertical jump task may be due to not imposing the cognitive demands that reflect sports participation. Objectives: To investigate the influence of additional cognitive demands on lower extremity mechanics during execution of the drop vertical jump task. Methods: Twenty uninjured women (age range, 18-25 years) were required to perform the standard drop vertical jump task, as well as drop vertical jumps that included additional cognitive demands. The additional cognitive demands were related to attending to an overhead goal (ball suspended overhead) and/or temporal constraints on movement selection (decision making). Three-dimensional ground reaction forces and lower extremity mechanics were compared between conditions. Results: The inclusion of the overhead goal resulted in higher peak vertical ground reaction forces and lower peak knee flexion angles in comparison to the standard drop vertical jump task. In addition, participants demonstrated greater peak knee abduction angles when trials incorporated temporal constraints on decision making and/or required participants to attend to an overhead goal, in comparison to the standard drop vertical jump task. Conclusion: Imposing additional cognitive demands during execution of the drop vertical jump task influenced lower extremity mechanics in a manner that suggested increased loading of the anterior cruciate ligament. Tasks utilized in anterior cruciate ligament injury risk screening may benefit from more closely reflecting the cognitive demands of the sports environment.